2018
DOI: 10.1093/dnares/dsy006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the DNA methyltransferases establishing the methylome of the cyanobacterium Synechocystis sp. PCC 6803

Abstract: DNA methylation in bacteria is important for defense against foreign DNA, but is also involved in DNA repair, replication, chromosome partitioning, and regulatory processes. Thus, characterization of the underlying DNA methyltransferases in genetically tractable bacteria is of paramount importance. Here, we characterized the methylome and orphan methyltransferases in the model cyanobacterium Synechocystis sp. PCC 6803. Single molecule real-time (SMRT) sequencing revealed four DNA methylation recognition sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 55 publications
0
43
0
Order By: Relevance
“…PCC 6803 (hereafter Synechocystis ), which does not express an active RM system. However, five different sites are methylated in the DNA of Synechocystis and the cognate methyltransferases were assigned (Scharnagl et al, 1998; Hagemann et al, 2018). Three DNA methyltransferases are encoded on the Synechocystis chromosome, M.Ssp6803I responsible for m5 CGATCG methylation, M.Ssp6803II for GG 4m CC, and M.Ssp6803III for the dam-like G m6 ATC methylation.…”
Section: Introductionmentioning
confidence: 99%
“…PCC 6803 (hereafter Synechocystis ), which does not express an active RM system. However, five different sites are methylated in the DNA of Synechocystis and the cognate methyltransferases were assigned (Scharnagl et al, 1998; Hagemann et al, 2018). Three DNA methyltransferases are encoded on the Synechocystis chromosome, M.Ssp6803I responsible for m5 CGATCG methylation, M.Ssp6803II for GG 4m CC, and M.Ssp6803III for the dam-like G m6 ATC methylation.…”
Section: Introductionmentioning
confidence: 99%
“…The first genome-wide study of m 5 C at base resolution was carried out by applying WGBS into E. coli and found cytosine methylation may take part in regulation of gene expression in stationary phase as a regulator ( Kahramanoglou et al, 2012 ). With respect to cyanobacteria, SMRT sequencing showed the existence of m 6 A in Microcystis ( Zhao et al, 2017 ), and Hagemann et al (2018) profiled the global DNA methylation (including m 6 A, m 4 C, and m 5 C) in Synechocystis by using combination of SMRT sequencing and WGBS, which indicated 5-methylcytosine and m 4 C in Synechocystis were in the context of m 5 CGATCG and GGm 4 CC, respectively. All these studies were conducted to determine the specificity of methyltransferases.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation for the differential influence of base outside of the target motif was found in E. coli K12 of mid-exponential phase, where the methylation level for CmCCWGG was lower than [ATG]mCCWGG (mCCWGG was the methyltransferase target motif) ( Kahramanoglou et al, 2012 ). Due to the partially resistance of m 4 C to the bisulfite-mediated deamination, the methylation level of GGm 4 CC context is much lower than that of m 5 CGATCG ( Hagemann et al, 2018 ). Consistent with this, our study also showed the methylation level of mCG methylation was higher than those of mCHG and mCHH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Top hits always included the highly iterative palindrome 1 (HIP1, 5′-GGCGATCGCC-3′) sequence. This sequence is a target of methylation in other cyanobacteria and may be involved in modes of DNA repair ( 48 , 49 ). However, its role in PCC 7002 remains unexplained.…”
Section: Methodsmentioning
confidence: 99%